Revisiting the issue of access to medicines in Africa: Challenges and recommendations - Yusuff Adebayo Adebisi; Ifechukwu Benedict Nwogu; Aishat Jumoke Alaran; Abubakar Olaitan Badmos; Adeboye Olakunle Bamgboye; Basirat Oluwadamilola Rufai; Osaretin Christabel Okonji; Malik O. Malik; John Oluwafemi Teibo; Samah Faisal Abdalla; Don Eliseo Lucero‐Prisno III; Mohamed Samai; et al. (Wiley, 2022)
Abstract Background Access to safe, effective, affordable, and quality medicines is an essential component of the right to health and is also one of the targets in the global development agenda. In this review article, we extensively discuss the challenges and issues surrounding access to medicines in the African region as well as provides recommendations for ensuring medicines security on the continent. Methods We conducted narrative review with the use of data reported in published literature, reports, and grey literature available in African countries on topics pertaining access to medicines. The authors also snowballed further data to gather information for this review and narrative synthesis was conducted. Results Africa faces a double burden of infectious and non‐communicable diseases and the need for effective universal access to medicines cannot be deemphasized. However, access to medicines on the continent is not without issues and challenges. Some of which are the high burden of infectious diseases and non‐infectious diseases, limited pharmaceutical industries and high costs of raw materials, overdependence on countries abroad for medicines, poor supply chain systems, lack of government investment in the pharmaceutical sector, unfavourable manufacturing conditions, limited health workforce, lack of sustainable health financing mechanisms, lack of infrastructures and technical know‐how, low investment on research and development, and circulation of fake and counterfeit medicines among others. Conclusion This review reifies that access to medicines in Africa faces numerous challenges and it emphasizes the urgent need to address these issues as the continent geared towards strengthening its health systems for universal health coverage.